PTEN regulates glioblastoma oncogenesis through chromatin-associated complexes of DAXX and histone H3.3 - Benitez, Jorge A. (Nat Commun, 2017)
Glioblastoma (GBM) is the most lethal type of human brain cancer, where deletions and mutations in the tumour suppressor gene PTEN (phosphatase and tensin homolog) are frequent events and are associated with therapeutic resistance. Herein, we report a novel chromatin-associated function of PTEN in complex with the histone chaperone DAXX and the histone variant H3.3. We show that PTEN interacts with DAXX and, in turn PTEN directly regulates oncogene expression by modulating DAXX-H3.3 association on the chromatin, independently of PTEN enzymatic activity. Furthermore, DAXX inhibition specifically suppresses tumour growth and improves the survival of orthotopically engrafted mice implanted with human PTEN-deficient glioma samples, associated with global H3.3 genomic distribution changes leading to upregulation of tumour suppressor genes and downregulation of oncogenes. Moreover, DAXX expression anti-correlates with PTEN expression in GBM patient samples. Since loss of chromosome 10 and PTEN are common events in cancer, this synthetic growth defect mediated by DAXX suppression represents a therapeutic opportunity to inhibit tumorigenesis specifically in the context of PTEN deletion.